Hydrodynamic Modelling of Tidally-Influenced Fluvial Zone, a study case of Palembang, Indonesia - Alamsyah Kurniawan; Andi Egon; Karina Aprilia Sujatmiko; Ardi Iman Malakani (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2022)
The development planning of a tidally-influenced fluvial zone poses a complex interaction between river discharge and its effect on the tidal patterns, especially in the dense population and high economic activity like Palembang located in South Sumatra Indonesia. Previous studies on numerical modelling in this area have focused on the flood; however, the hydrodynamic modelling described interaction between river discharge and tidal is not described in more detail. The present study aims to better understand the zone by using a combination of numerical modelling and qualitative assessment of in situ measurement data. Hence, the water level condition in the study area is a mix of tidal and river discharge. A 2D-hydrodynamic modeling has been successfully conducted to assess their interaction in this zone properly by using the commercial software, called MIKE21 FM. This study describes setting up the computational model, boundary location, type of forcing (tidal and non-tidal), bedform roughness, turbulent viscosity and extensive calibration and validation. In situ measurement indicates that the site's water level and flow characteristic is complex, a mixture of tidal force from the downstream and river flows from the upstream in which seasons play an important role. It is found that comparing model outputs and the measurement data in the study area for the validation and verification process effectively describes the hydrodynamic condition in the fluvial-estuarine transition area of Palembang. As the model shows good reliability, the long term hydrodynamic in line with transport model should be developed to support the Palembang area rapid development.